Pengaruh User Experience, Discount dan Kemudahan Akses terhadap Keputusan Pembelian pada Pengguna Grabfood (Studi pada Mahasiswa Manajemen UNISMA Angkatan 2018) - Putri Ekawati; Nur Hidayati; Etty Saraswati (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThe purpose of this research is to describe user experience, discount, ease of access and purchasing decision and to know the influence of user experience, discount and ease of access to purchasing decision on Grabfood user. The method in this research is using quantitative method. The sample of this research is student of Faculty of Economic and Business Department of Management 2018 Islamic University of Malang by using non probability sampling that is purposive sampling, that is counted 86 respondents. Methods in using data using questionnaires. The analysis process used in this research is the multiple regression analysis. The result of this research indicate user experience, discount and ease of access has positive and significant effect to purchasing decision on Grabfood user. Keywords : User Experience, Discount, Ease of Access, Purchasing Decision